Development of a food-based index of dietary inflammatory potential for Koreans and its relationship with metabolic syndrome - Na, Woori (Nutr Res Pract, 2019)
BACKGROUND/OBJECTIVES: Inflammation is known to be a risk factor for metabolic diseases. This study aimed to develop a Food-based Index of Dietary Inflammatory Potential (FBDI) and examine its association with metabolic biomarkers. SUBJECTS/METHODS: This study analyzed the raw data from the 2012-2014 Korean Genome and Epidemiology Study data of 17,771 people. To analyze the relationship between foods consumed by Koreans and inflammation, we conducted a correlation analysis between 51 food groups and hs-CRP levels. The FBDI was developed from 17 food groups selected by multiple regression method. We examined whether FBDI was associated with metabolic markers (waist circumference, blood pressure, fasting glucose, triglyceride, and HDL-cholesterol) in the 6th Korea National Health and Nutrition Examination Survey (KNHANES). We used binary logistic regression analysis to examine the association. RESULTS: The FBDI model included seven of the anti-inflammatory food groups and three of the pro-inflammatory food groups. The FBDI formula was calculated by multiplying the intake of food group by β-coefficients derived from the multiple regression model based on the correlation analysis. The FBDI was significantly associated with waist circumference (P < 0.001), blood pressure (P < 0.001), triglyceride level (P < 0.001), and HDL-cholesterol (P < 0.001) level among adults aged 20–64 years in the KNHANES. The prevalence of metabolic syndrome was 2.618 times higher in the group with the highest FBDI than in the group with the lowest one (95% confidence interval: 1.778–3.856, P for trend < 0.001). CONCLUSIONS: This study established an FBDI reflecting food intake patterns of Koreans, which showed a significant relationship with the prevalence of metabolic syndrome.